2006
DOI: 10.1111/j.1399-3046.2006.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric renal transplantation in a South African teaching hospital: A 20‐year perspective

Abstract: Pediatric renal transplantation in Johannesburg can be accomplished with low complication rates, but medium and long-term graft survival is poor when compared with contemporary results achieved in developed countries. The difficulties of undertaking such complex, multidisciplinary interventions in a developing nation are daunting, but we believe that renal transplantation should still be the treatment of choice for all children with ESRF. The poorer outcomes in black recipients can be addressed by increasing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) reviewed 282 paediatric transplants from 1984 to 2003. [13] Ten-year recipient and graft survival rates were 68% and 23%, respectively. Red Cross War Memorial Children's Hospital (RCWMCH) in Cape Town reviewed 89 transplants from 1995 to 2005 and found the 7-year graft survival rate to be 72%.…”
Section: Researchmentioning
confidence: 99%
“…Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) reviewed 282 paediatric transplants from 1984 to 2003. [13] Ten-year recipient and graft survival rates were 68% and 23%, respectively. Red Cross War Memorial Children's Hospital (RCWMCH) in Cape Town reviewed 89 transplants from 1995 to 2005 and found the 7-year graft survival rate to be 72%.…”
Section: Researchmentioning
confidence: 99%
“…Available resources [7, 14] affect patient selection, follow-up and drug regimens. Community attitudes influence decisions regarding treatment of high-risk patients such as neonates and children with handicaps [15].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Further, there exist pervasive racial and ethnic disparities in kidney transplantation in both the adult and pediatric setting. [47] While much of the research examining this issue has been conducted in the United States, similar disparities have been identified in Australia[8], Belgium[7], Canada[9] the Netherlands[7], South Africa[10], and the United Kingdom[11] among others, indicating the global nature of this issue. Although it is important to note that some of these disparities may be the result of factors that are beyond the control of the medical system (e.g., co-morbidities and hereditary diseases that are associated with certain ethnic groups), [12, 13] studies have repeatedly demonstrated that differences in medical factors alone are not sufficient to explain the disparities in transplantation in their entirety.…”
Section: Introductionmentioning
confidence: 82%
“…There are clear disparities in post-transplant outcomes as well[7, 10, 17, 41]. A 2007 analysis of the over 6287 pediatric patients who had been registered in the NAPRTCS database demonstrated that 5-year graft survival rates for AA children were significantly lower than for white children (65.6% versus 83.1%).…”
Section: Disparities In Transplant Outcomes and Post-transplant Carementioning
confidence: 99%
See 1 more Smart Citation